2010
DOI: 10.1007/s11581-010-0441-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrodialytic desalination of brackish water: effect of process parameters and water characteristics

Abstract: The aim of this work is to study the desalination of brackish water using a laboratory scale electrodialysis cell. The influence of several parameters, such as flow rates, initial feed concentration, applied voltage and circulation mode on process efficiency were studied. This efficiency is evaluated by the demineralization rate, ionic flux transport and current efficiency. In this study, experiments were carried out on synthetic brackish water solutions prepared from sodium chloride salts. The concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…This result can be explained by the concentration polarization phenomenon which is more important at high concentration (Sadrzadeh and Mohammadi 2008). As demonstrated in previous studies (Kabay et al 2002;Banasiak et al 2007;Sadrzadeh and Mohammadi 2008;Ben Sik Ali et al 2010a), the number of ions transported through the membranes are almost the same but total amounts of salts are quite different from the different treated solution. As known, the calculation of DR depends strongly on the initial feed concentration and the amount of transported ions.…”
Section: Main Effects Plotsupporting
confidence: 54%
See 3 more Smart Citations
“…This result can be explained by the concentration polarization phenomenon which is more important at high concentration (Sadrzadeh and Mohammadi 2008). As demonstrated in previous studies (Kabay et al 2002;Banasiak et al 2007;Sadrzadeh and Mohammadi 2008;Ben Sik Ali et al 2010a), the number of ions transported through the membranes are almost the same but total amounts of salts are quite different from the different treated solution. As known, the calculation of DR depends strongly on the initial feed concentration and the amount of transported ions.…”
Section: Main Effects Plotsupporting
confidence: 54%
“…Sadrzadeh and Mohammadi (2008) and Ben Sik Ali et al (2010a) observed that the salt percent removal increases when the flow rates decrease. They suggested that for low flow rates the residence time of ions in the dilute compartment increases.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…As mentioned before, the electrodialysis is an electro membrane process especially used for the desalination of brackish water and sodium chloride recovery from sea water [10,13]. The transfer of ionic components from aqueous solution through ion exchange membranes is carried out under the driving force of an electrical field.…”
Section: Introductionmentioning
confidence: 99%